1989
DOI: 10.2527/jas1989.67123250x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameters for Ewe Productivity Traits in the Columbia, Suffolk and Targhee Breeds

Abstract: Estimates of repeatability and heritability were obtained for the following productivity traits of ewes: litter weight at birth (LWB) and weaning (LWW), litter size at birth (LSB), litter size alive at birth (NBA), litter size at weaning (LSW), neonatal survival rate (SRB) and preweaning survival rate (SRW). Phenotypic and genetic correlations were estimated for litter traits. The data set contained 6,394 ewe breeding records from three state stations over 10 yr on 1,731 ewes that were the progeny of 488 sires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
11
6
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 0 publications
9
11
6
1
Order By: Relevance
“…The estimate was in good agreement with the estimate of 0.03 litter size at birth and for 0.18 litter size at weaning reported for Suffolk ewe by Nakagawa et al (2005) and for 0.11 litter size at weaning and for 0.17 litter size at weaning estimated for Polypay sheep by Hanford et al (2006), and for 0.17 litter size at weaning reported for three sheep by Abdulkhaliq et al (1989), and Hagger (2002) found 0.066 to 0.136 for heritability of litter size in different sheep breeds.…”
Section: Prolificacy Traitssupporting
confidence: 80%
See 1 more Smart Citation
“…The estimate was in good agreement with the estimate of 0.03 litter size at birth and for 0.18 litter size at weaning reported for Suffolk ewe by Nakagawa et al (2005) and for 0.11 litter size at weaning and for 0.17 litter size at weaning estimated for Polypay sheep by Hanford et al (2006), and for 0.17 litter size at weaning reported for three sheep by Abdulkhaliq et al (1989), and Hagger (2002) found 0.066 to 0.136 for heritability of litter size in different sheep breeds.…”
Section: Prolificacy Traitssupporting
confidence: 80%
“…The estimates of direct heritability for prolificacy and lamb weight traits in literatures have ranged from 0.03 to 0.18 for litter size at birth, 0.13 to 0.18 for litter size at weaning (Abdulkhaliq et al, 1989;Hanford et al, 2006;Ekiz et al, 2005;Ligda et al, 2000;Hanford et al, 2003;Noter and Hough, 1997;Hagger, 2002), and 0.00 to 0.18 for survival rate (Abdulkhaliq et al, 1989;Long et al, 1989;Wyk et al, 2003;Fogarty, 1995). Reported estimates direct heritability for different sheep breeds range from 0.00 to 0.38 for lamb birth weight, 0.025 to 0.49, for weaning weight (Babar et al, 2003;Bahreini et al, 2007;Duru and Koyuncu, 2005;Hanford et al, 2006;Ligda et al, 2000;Maria et al, 1993;Carrillo and Segura, 1993;Hanford et al, 2003;Nakagawa et al, 2005;Noter and Hough, 1997;Ozcan et al, 2005;Reale et al, 1999;Sawalha et al, 2005;Szwaczkowski et al, 2006;Tosh and Kemp, 1994;Wuliji et al, 2001;Wyk et al, 2003) and 0.12 to 0.25 for yearling weights (Reale et al, 1999;Ozcan et al, 2005), and 0.11 to 0.33 for average daily gain (Carrillo and Segura, 1993;Maria et al, 1993;Noter and Hough, 1997;Ozcan et al, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…The heritability for LW was 0.200, with an HPD95 that ranged between 0.087 and 0.277. Although the genetic component of LW has not been widely analysed in sheep, our heritability estimate was comparable with those reported by Abdulkhaliq et al (1989) in Columbia, Suffolk and Targhee breeds, and higher than the heritability observed in Moroccan sheep breeds (El Fadili and Leroy, 2001). Nevertheless, these values were lower than the ones reported in pigs (Sorensen et al, 2000).…”
Section: Resultscontrasting
confidence: 35%
“…Previously, researchers identified increasing litter size at birth or weaning as the single most useful criterion to improve reproductive efficiency or net reproductive rate (Turner 1969;Clarke 1972;Turner 1978). Recently, the trait of interest has been the total weight of lamb(s) weaned per ewe joined or lambing (Ercanbrack and Knight 1985;Lasslo et al 1985;Abdulkhaliq et al 1989;Fogarty 1994;Cloete et al 2004). Litter weight weaned per breeding ewe is an appropriate biological measure of overall ewe reproduction and productivity (Martin and Smith 1980;Ercanbrack and Knight 1998;Snowder 2002;Afolayan et al 2007).…”
Section: Defining Reproduction and Ewe Productivitymentioning
confidence: 99%